The role of carbon capture and sequestration policies for climate change mitigation - Matthias Kalkuhl; Ottmar Edenhofer; Kai Lessmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper takes the policy failure in establishing a global carbon price for efficient emissions reduction as a starting point and analyzes to what extent technology policies can be a reasonable second-best approach. From a supply-side perspective, carbon capture and storage (CCS) policies differ substantially from renewable energy policies: they increase fossil resource demand and simultaneously lower emissions. We show in a theoretical model that, under idealized conditions, a pure CCS subsidy can be as efficient as a carbon tax. Within a numerical dynamic general equilibrium model, we analyze CCS and renewable energy policies under more realistic parameter settings for imperfect or missing carbon prices. We find that in contrast to renewable energy policies, CCS policies are not always capable of reducing emissions in the long run. If feasible, CCS policies carry often lower social costs compared to renewable energy policies. In case fossil resources are abundant and renewable energy costs low, renewable energy policies perform better. Our results indicate that a pure CCS policy or a pure renewable energy policy carry specific risks of missing the environmental target. A smart combination of both, however, can be a robust and low-cost temporary second-best policy.
Keywords: Q31; Q38; Q40; Q54; Q58; 330; renewable energy subsidy; supply-side dynamics; green paradox; carbon pricing; global warming; CCS; Klimaschutz; Förderung regenerativer Energien; Kohlenstoffsenke; Subvention; Second Best; Theorie